Criteria for predicting the development of recurrent peripheral nerve sheas tumors - A. Yu. Orlov; A. S. Nazarov; A. A. Dolgushin; D. A. Murzaeva; Yu. V. Belyakov; E. A. Oleynik; A. V. Kudziev; Yu. M. Zabrodskaya (Сибирский онкологический журнал, 2024)
Peripheral nerve sheaths tumors (PNST) account for about 8 % of all nervous system cancers. The relapse rate ranges from 17.3 to 26.4 %, showing an upward trend. The causes and provoking factors for the development of relapses of PNST have not been fully studied. Purpose of the study: to establish criteria for predicting recurrence of PNST. Material and Methods. The study included 122 patients who were treated at the Department of Spine and Peripheral Nerve Surgery of A.I. Polenov Russian Research Neurosurgical Institute from 2009 to 2021. Among them, there were 87 (71.3 %) patients with primary PNST and 35 (28.7 %) patients with recurrent PNST. All patients underwent MRI and ENMG both before and after surgery. An immunohistochemical study of Ki67 and SO X10 markers was performed. Results. The majority of relapses occured within 1 year after surgery. In cases with radical removal of PNST, the risk of relapse was: 28.6 % for schwannomas 28.6 %, 37.1 % for neurofibromas and 34.3 % for MP NST 34.3 % (p≥0.05). The risk of developing relapse of PNST was 2.9 times higher in patients aged ≥49 years than in patients aged ≤48 years (p<0.004). The larger the initial size of the tumor, the higher the risk of relapse in the late postoperative period. The risk of developing relapse of MP NST was 8.79 times higher in patients with tumor size of greater than 11.5 cm than in patients with smaller tumor size (p<0.02). The of Ki67 level above 4.85 % in schwannomas and above 5.17 % in neurofibromas can predict relapse of PNST (p<0.05). Loss of SO X10 protein expression was associated with an increase in histological anaplasia of the tumor, which causes a high risk of relapse and an unfavorable clinical course of the disease. Conclusion. Despite radical (total) resection of PNST, the risk of relapse remains high. The pathological type of tumor, its size, levels of SO X10 and Ki67 markers, patient’s age, degree of preoperative neurological deficit and extent of surgery are significant criteria for predicting the development of relapse of PNST.